2023
DOI: 10.1021/acs.organomet.2c00578
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonium-Pincer Ligands Flexibility in Pt(II) Complexes

Abstract: The coordination chemistry of sulfonium cations, dormant since the early nineties, was recently revived when we reported the synthesis and characterization of the first Rh(I) and Pt(II) pincer-sulfonium complexes. With the Pt(II) complexes, we had noticed the hemilability of our sulfonium-pincer ligands further explored here. This hemilability led to mononuclear bidentate complexes with both the aromatic and aliphatic sulfonium ligands. With the latter, due to its flexibility, dimeric structures of two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The 1 J Pt-P of 2037 Hz exhibited by the tris-cationic sulfonium complex [6](BF 4 ) 3 is significantly smaller than that of [5](OTf) 2 (Table 1, entry 3), as well as that of other bis-cationic sulfonium Pt(II) complexes we reported earlier (Table S3, entries 1-3). [9] It is also lower in comparison to the values reported for the Pt(II) and Pt(0) complexes of other cationic and bis-cationic pincer ligands (Table S3, entries 4-8). [16,17] The highly electrophilic character of Pt in [6](BF 4 ) 3 was further supported by the NBO calculations (ωB97X-D3/ Def2-TZVP) we performed on the optimized model analogs of the Pt complexes mentioned above (where t Bu and Ph groups were replaced by H atoms for simplicity).…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…The 1 J Pt-P of 2037 Hz exhibited by the tris-cationic sulfonium complex [6](BF 4 ) 3 is significantly smaller than that of [5](OTf) 2 (Table 1, entry 3), as well as that of other bis-cationic sulfonium Pt(II) complexes we reported earlier (Table S3, entries 1-3). [9] It is also lower in comparison to the values reported for the Pt(II) and Pt(0) complexes of other cationic and bis-cationic pincer ligands (Table S3, entries 4-8). [16,17] The highly electrophilic character of Pt in [6](BF 4 ) 3 was further supported by the NBO calculations (ωB97X-D3/ Def2-TZVP) we performed on the optimized model analogs of the Pt complexes mentioned above (where t Bu and Ph groups were replaced by H atoms for simplicity).…”
Section: Methodsmentioning
confidence: 67%
“…In our earlier study, [9b] we showed that flexible PSP‐based sulfonium pincer ligands I and II were found to undergo an easy interconversion between a trans ‐κ 3 ‐PSP and a cis ‐κ 2 ‐PP mode that was always accompanied by a trans‐ to‐ cis isomerization of the phosphines (Scheme 2a). Therefore, maintaining the trans geometry seems to be essential in preserving the Pt−S coordination.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation